Prevalence and factors associated with contraception usage among Orang Asli in Jempol, Negeri Sembilan - Izudin, Muhamad; Mohd Arif, Nur Yasmeen Dafeena; Dapari, Rahmat; Basri, Nurul Iftida (Springer Nature, 2025)
Background: Contraceptive use among the Orang Asli (OA), an indigenous group in Malaysia, is likely influenced by the availability and accessibility of healthcare services. Understanding their contraceptive usage is crucial for effective family planning strategies. This study aims to determine the prevalence of contraceptive usage and associated factors among residents of a village in Jempol, Negeri Sembilan, Malaysia. Methodology: This cross-sectional study was conducted through structured interviews utilizing a validated questionnaire. Eligible participants were invited through a liaison person of the village to answer the questionnaire. The questionnaire comprised five sections: socio-demographic data, knowledge of contraception, usage of contraception, methods of contraception used, and reasons for using or not using contraception. Mann–Whitney U and Chi Square test were used to test the association between contraception use and independent variables. p ≤ 0.05 was considered as significant. Results: A total of 88 OA individuals were interviewed, revealing that 50 respondents (56.8%) reported using contraception, while 38 (43.2%) did not. The majority of respondents had no formal education or only had primary education (71.6%). Most were employed (73.9%), with a median monthly income of RM500. The median knowledge score regarding contraception was 5 out of 10. Among those using contraception, oral contraceptive pills were the most common method used (84.3%). Female respondents used contraception significantly more than male respondents (p = 0.001), with higher usage observed among married individuals (p = 0.000) and those with children (p = 0.000). Moreover, a higher knowledge score was significantly associated with increased contraceptive use (p = 0.026). Conclusion: The findings emphasize the critical role of socioeconomic factors and awareness in contraceptive use among the Orang Asli. Targeted interventions aimed at improving knowledge and accessibility to contraceptive methods could lead to enhanced usage and better maternal and child health outcomes.